Differential DNA Methylation and Cardiometabolic Risk in African American Mother-Adolescent Dyads. Issue 1 (January 2022) - Gentry, Amanda Elswick; Robins, Jo; Makowski, Mat; Kliewer, Wendy
Background: Cardiovascular disease disproportionately affects African Americans as the leading cause of morbidity and mortality. Among African Americans, compared to other racial groups, cardiovascular disease onset occurs at an earlier age due to a higher prevalence of cardiometabolic risk factors, particularly obesity, hypertension and type 2 diabetes. Emerging evidence suggests that heritable epigenetic processes are related to increased cardiovascular disease risk, but this is largely unexplored in adolescents or across generations. Materials and Methods: In a cross-sectional descriptive pilot study in low-income African American mother-adolescent dyads, we examined associations between DNA methylation and the cardiometabolic indicators of body mass index, waist circumference, and insulin resistance. Results: Four adjacent cytosine and guanine nucleotides (CpG) sites were significantly differentially methylated and associated with C-reactive protein (CRP), 62 with waist circumference, and none to insulin resistance in models for both mothers and adolescents. Conclusion: Further study of the relations among psychological and environmental stressors, indicators of cardiovascular disease, risk, and epigenetic factors will improve understanding of cardiovascular disease risk so that preventive measures can be instituted earlier and more effectively. To our knowledge this work is the first to examine DNA methylation and cardiometabolic risk outcomes in mother-adolescent dyads.